Glutaraldehyde Fixation of Human Blood Platelets - Sixma, J. J; Linssen, W. H; Geuze, H. J (Thrombosis and Haemostasis, 1972)
Hypertonic glutaraldehyde solutions produce dilatation of the surface connected system and shrinking of the cytoplasma. Hypertonic solutions produce swelling of the platelets. Good results are obtained with 1% glutaraldehyde M 0.07 M phosphate buffer (275 mosmol) 4 parts to 1 part platelet rich plasma. High glutaraldehyde concentrations do not affect the platelet ultrastructure.